The Sleep Quality of the Frontline Healthcare Workers and the Improving Effect of Tai Chi - Zhan, Jingye; Yang, Kangdi; Sun, Zhuoer; Bai, Lingling; Lu, Xiaoying; Wang, Xiuhong; Liu, Weizhi; Yi, Chen; Wang, Lina (Frontiers in Psychiatry, 2022)
Background A number of studies have documented that coronavirus disease 2019 (COVID-19) brought more negative impact on the physical and psychological functioning of frontline healthcare workers. Especially, sleep quality was focused. This study aimed to investigate the sleep quality of frontline healthcare workers, risk factors for sleep quality, and the effect of Tai Chi training. Methods A total of 98 frontline healthcare workers were recruited, coming from the infection department, fever clinic, laboratory, and medical imaging department in a COVID-19-designated hospital in Shanghai. Of them, 50 participated in a 2-week intervention and were randomized to receive a Tai Chi training or relaxation training. Participants were assessed at baseline, 7 and 14 days after participation. Demographic information, sleep quality, and anxiety were measured by using the demographic questionnaire, Pittsburgh Sleep Quality Index (PSQI) and Beck Anxiety Inventory (BAI). Results 13.3% participants were above the cut-off score (>10) for the PSQI. Regression analysis showed gender, age, working years, and job category had effect on sleep quality. Compared to the control group, participants in the Tai Chi training group had lower scores on both PSQI (p < 0.05) and BAI (p < 0.01) after the 2-week intervention. Conclusion It was demonstrated that poor sleep quality existed in the frontline healthcare workers, which was related to gender, age, working years, and job category. Tai Chi training can dramatically improve their sleep quality and reduce anxiety symptoms.